Heteromerization fingerprints between bradykinin B2 and thromboxane TP receptors in native cells - Dagher, Oula K. (PLoS One, 2019)
Bradykinin (BK) and thromboxane-A(2) (TX-A(2)) are two vasoactive mediators that modulate vascular tone and inflammation via binding to their cognate “class A” G-protein coupled receptors (GPCRs), BK-B2 receptors (B2R) and TX-prostanoid receptors (TP), respectively. Both BK and TX-A(2) lead to ERK1/2-mediated vascular smooth muscle cell (VSMC) proliferation and/or hypertrophy. While each of B2R and TP could form functional dimers with various GPCRs, the likelihood that B2R-TP heteromerization could contribute to their co-regulation has never been investigated. The main objective of this study was to investigate the mode of B2R and TP interaction in VSMC, and its possible impact on downstream signaling. Our findings revealed synergistically activated ERK1/2 following co-stimulation of rat VSMC with a subthreshold dose of BK and effective doses of the TP stable agonist, IBOP, possibly involving biased agonist signaling. Single detection of each of B2R and TP in VSMC, using in-situ proximity ligation assay (PLA), provided evidence of the constitutive expression of nuclear and extranuclear B2R and TP. Moreover, inspection of B2R-TP PLA signals in VSMC revealed agonist-modulated nuclear and extranuclear proximity between B2R and TP, whose quantification varied substantially following single versus dual agonist stimulations. B2R-TP interaction was further verified by the findings of co-immunoprecipitation (co-IP) analysis of VSMC lysates. To our knowledge, this is the first study that provides evidence supporting the existence of B2R-TP heteromerization fingerprints in primary cultured VSMC.